Morphometric traits, carcass characteristics and biochemical composition of meat between local and synthetic Algerian rabbit genotypes - Sanah, I.; Boudjellal, A.; Becila, S. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
The aim of this research was to study the genetic and sex effects on morphometric traits, carcass characteristics and biochemical composition of rabbit meat of two Algerian breeds, local population and synthetic line (ITELV2006). For this purpose, 60 animals (30 per group) from 90 d of age were used. The body weight and the morphometric traits recorded were determined using a digital weighing scale and flexible tape. At slaughter, carcass traits, and biochemical meat quality characteristics such us protein, fat, ash, moisture content and fatty acids composition were measured. The results obtained revealed that the synthetic line has higher values of morphometric measurements than the local breed. The sex factor and the interaction genotype X sex had a significant effect only on chest circumference (P < 0.05). It is also observed, that the majority of carcass characteristics were more affected by genetic than by genetics. Which body weight at slaughter of males and females derived from synthetic lines were 41% and 22% higher than local rabbits respectively. Furthermore, the new line displayed a good meat yield (60%) with a higher mean value (+ 5%) of dressing out % rather than the local one. Regarding, the proximate biochemical composition of meat, the synthetic line has shown also the highest content of protein and fat (P < 0.05). Concerning with fatty acids profile; the local breed exhibited the highest content of n3 and n6 polyunsaturated fatty acids (n3 and n6 PUFAs), consequently, the lower value of n-6: n-3 ratio (9.82) and the highest value of polyunsaturated fatty acids to saturated fatty acids (PUFAs/SFAs: 0.73). Finally, it should be emphasized that the relevant differences recorded in this experiment are assumed to be primarily genetic, thus, sex might be regarded as a minor factor. The synthetic showed better characteristics due to its genetic potential. Therefore, it is recommended to be used for Algerian meat production.